Natural convective heat transfer and nanofluid flow in a cavity with top wavy wall and corner heater - Sheremet, Mikhail A.; Pop, Ioan; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Springer, 2016)
A numerical analysis of natural convection of nanofluid in a wavy-walled enclosure with an isothermal corner heater has been carried out. The cavity is heated from the left bottom corner and cooled from the top wavy wall while the rest walls are adiabatic. Mathematical model has been formulated using the single-phase nanofluid approach. Main efforts have been focused on the effects of the dimensionless time, Rayleigh number, undulation number, nanoparticle volume fraction and length of corner heaters on the fluid flow and heat transfer inside the cavity. Numerical results have been presented in the form of streamlines, isotherms, velocity and temperature profiles, local and average Nusselt numbers. It has been found that nanoparticle volume fraction essentially affects both fluid flow and heat transfer while undulation number changes significantly only the heat transfer rate.
Keywords: wavy cavity; natural convection; nanofluid; corner heater; numerical results